Five words : critical semantics in the age of Shakespeare and Cervantes - Greene, Roland, 1957- (University of Chicago Press, 2013)
Blood. Invention. Language. Resistance. World. Five ordinary words that do a great deal of conceptual work in everyday life and literature. In this original experiment in critical semantics, Roland Greene considers how these five words changed over the course of the sixteenth century and what their changes indicate about broader forces in science, politics, and other disciplines. Greene discusses a broad swath of Renaissance and transatlantic literature-including Shakespeare, Cervantes, Camões, and Milton-in terms of the development of these words rather than works.